1999
DOI: 10.1002/(sici)1097-4644(19990801)74:2<292::aid-jcb13>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the participation of protein kinase C ? in the proliferation of cultured myoblasts

Abstract: There is evidence involving protein kinase C (PKC) in the signal transduction pathways that regulate the differentiation of myoblasts into mature multinucleated muscle cells (myotubes). In order to obtain information on the possible role of individual PKC isozymes in myogenesis, in the present work we investigated the differential expression of PKC isoforms alpha, beta, delta, epsilon, and zeta during muscle cell development in vitro. Chick embryo myoblasts cultured from 1 to 6 days were used as experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
21
2
Order By: Relevance
“…These differences in results might be because of the cell types, induction time, drug doses, or means of administration. Although the activation of the PKC signaling pathway is reported to be involved in myogenesis [26], we found no significant change in total PKC or phosphorylated PKC in 5-Aza-treated hucMSCs. This indicated that PKC activation was not the major mechanism responsible for 5-Aza-induced hucMSC differentiation into cardiomyocytes.…”
Section: Discussioncontrasting
confidence: 88%
“…These differences in results might be because of the cell types, induction time, drug doses, or means of administration. Although the activation of the PKC signaling pathway is reported to be involved in myogenesis [26], we found no significant change in total PKC or phosphorylated PKC in 5-Aza-treated hucMSCs. This indicated that PKC activation was not the major mechanism responsible for 5-Aza-induced hucMSC differentiation into cardiomyocytes.…”
Section: Discussioncontrasting
confidence: 88%
“…PKCα is involved in signal transduction cascades regulating the proliferation of myoblasts (Goel and Dey, 2002). Furthermore, PKCα is engaged in repressing myogenic factors, in particular MyoD (Vaidya et al, 1991), suggesting its role as a negative modulator of myogenesis (Capiati et al, 1999). Interestingly, Ryr1 activity had been related to both PKCα activation and MyHC-slow gene suppression.…”
Section: Discussionmentioning
confidence: 99%
“…By this time, myoblasts become differentiated into myotubes with both biochemical and morphological characteristics of adult skeletal muscle fibers [Capiati et al, 1999].…”
Section: Cell Culturementioning
confidence: 99%